The meeting of the "Communist Parties" suggested by Brezhniev - a new plot hatched by Krushchovite revisionists against Marxism-Leninism and revolution. [Transl.] ("Naim Frashëri", 1967)
Repr.: "Zëri i Popullit". 1966, December 13.